Benefit-cost analysis of Uganda’s clonal coffee replanting program: An ex-ante analysis - Benin, Samuel; You, Liangzhi (International Food Policy Research Institute, 2007)
The Ugandan coffee industry is facing some serious challenges, including low international prices in the international coffee market, aging coffee trees and declining productivity, and, more recently, the appearance of coffee-wilt disease, which have all contributed to the decline in both the quantity and value of coffee exports. The government of Uganda, through the Uganda Coffee Development Authority (UCDA), in 1993/94 started a coffee-replanting program to both replace coffee trees that were old or affected by coffee-wilt and expand coffee production into other suitable areas in northern and eastern Uganda. This program seems to be helping to both combat the industry’s problems and reverse the declining trends. However, the UCDA announced in 2004 that it was withdrawing from the replanting program in the 2004/05 season (it had supported nursery operators and purchased and distributed free seedlings to farmers), so the program’s achievements may not last. This paper estimates the economic returns (benefit–cost ratio) of the coffee-replanting program, particularly replanting with clonal varieties, and analyzes the welfare implications of the decision to withdraw. We find that the internal rate of return (IRR) and benefit–cost ratio are very high, about 50 percent and 3.7 respectively, suggesting that the replanting program in Uganda is very beneficial to the livelihoods of coffee farmers, the coffee sub-sector, and the economy as a whole. The largest benefits occur in the central region, where the bulk of coffee is grown, followed by the eastern and western regions. The largest return on investment occurs in the eastern region, followed by the central and western regions. Sensitivity analyses show that the results (that is, the net benefits) are robust with respect to the assumptions made, including demand and supply elasticities and level of domestic consumption. Although the results are sensitive to farm production costs and coffee yields, the program still improves welfare. Taken all together, the results suggest that if the government withdraws from the replanting program without putting place adequate alternative measures to ensure the program’s sustainability, welfare will be severely reduced in coffee-growing areas.